“Perpetual peace and friendship”: the Cherokee-Confederate Coalition in the American Civil War - Tindle, James Franklin (Kansas State University, 2019)
The partnership between the Confederacy and the Cherokee Nation grew out of an acknowledgement of mutual interests and goals. The Confederacy wanted to expand pro-slavery influence further west, strengthen the Southern economy by acquiring natural resources and establishing foreign trade, and protect the western frontier from invasion by the federal government. The Cherokee Nation wanted the means to defend themselves against foreign and domestic threats, funds to care for their suffering people, and full recognition as a sovereign, independent country. Both parties viewed the other as the key to reaching these objectives, and the subsequent collaboration yielded impressive results. Confederate commissioners approached all five so-called “Civilized Tribes” in Indian Territory in May 1861, hoping to convince them to join the secession movement. Southern leaders in Richmond had authorized these representatives to offer generous terms, including protection against internal and external threats, legal and political independence, and partial representation in the Confederate government. The debate about whether or not to accept these terms split the Cherokee Nation apart, resurrecting decades old feuds and unsettled disagreements. The largest and most influential faction, led by Principal Chief John Ross, favored neutrality, while the second major party, led by Stand Watie, jumped at what they saw as the chance to shape the future of their tribe and protect themselves against their bitter rivals. As pressure from Richmond and the Watie faction increased, Ross and his followers eventually had to admit the Cherokee Nation had little choice but to join the Confederacy. On October 7, 1861, Chief Ross signed a formal treaty with the South, declaring “perpetual peace and friendship” between the two nations. However, soon after the Cherokee chose sides, Northern troops captured Ross and conducted him to Washington, prompting many tribal leaders to disavow the treaty and declare their loyalty to the Union. With the approval of Confederate officials, Stand Watie took over as Principal Chief, leading the Southern-recognized tribal government for the rest of the war. Despite this rocky beginning and subsequent challenges, the Cherokee-Confederate coalition functioned well and accomplished many objectives. The partnership was instrumental in maintaining the Southern war effort in the West, and the Cherokee Nation would have collapsed completely without Confederate assistance. Although the majority of military operations west of the Mississippi River soon devolved into a protracted guerrilla conflict, the units under Watie’s command cooperated well with their white allies and achieved great success in that region’s irregular warfare. Although the coalition was unable to change the course of the Civil War in the western theater, both Confederate and Cherokee leaders agreed the partnership had provided vital assistance for both parties involved. The South was unable to fulfill every promise in the treaty but managed to provide desperately needed economic and military aid for their allies in Indian Territory. The Cherokee were unable to tip the balance in favor of the South, but without their help the war in the West would have ended much sooner.
Keywords: Native Americans; American Civil War; American south; American military history; American west; Coalition warfare